Religious Diversity and Dialogue: A Buddhist Perspective - Tilakaratne, Asanga (Interreligious Studies and Intercultural Theology, 2020)
With the understanding that one’s views on religious diversity shapes one’s attitude to interreligious dialogue, in this article I try to articulate how the Buddha perceived the phenomenon of religious diversity and then to discuss how this perception could inform the Buddhist practice of interreligious dialogue. I begin this discussion with reference to the diversity of views held by the Roman Catholics themselves on interreligious dialogue and the Colonial and more recent history of dialogue in the local context of Sri Lanka. Next I move on to discuss Buddhism’s own self-understanding as a non-theistic system. In order to support the non-theistic claim of Buddhism I produce two arguments, one philosophical and the other experiential, both derived from the discourses of the Buddha. Having supported the non-theist stance of Buddhism, I propose that the Buddhist attitude is to be open to religious diversity while upholding the position that nirvana is the ultimate goal irreducible to any other similar goals. The discussion shows that to accept diversity is not necessarily to accept pluralism in religion, and that this position does not preclude Buddhists from engaging in interreligious dialogue.